Introduction to Computer Graphics - Eck, David J. (Open textbook library., 2016)
Introduction to Computer Graphics is a free, on-line textbook covering the fundamentals of computer graphics and computer graphics programming. This book is meant for use as a textbook in a one-semester course that would typically be taken by undergraduate computer science majors in their third or fourth year of college.